HUMAN ACTIVITIES - PRIMARY CAUSE OF DENGUE AND ZIKA - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 11 February 2016 – Urbanisation, climate change and changes in vector biology were the main causes behind the rapid rise in the mosquito vector population, especially the infamous Aedes aegypti mosquito (http://www.cdc.gov/dengue/resources/30Jan2012/aegyptifactsheet.pdf)es, which carry the dengue and zika virus.